If $a-b=3$, $a+b+x=2$, then find the value of $(a-b)\left(x^3-2ax^2+a^2x-(a+b)b^2\right)$
I could only substitute the value of $a-b$ there. I seriously want to try as much as I can on my own but I don't even know where to start.
I tried WolframAlpha but it seems to mess up the polynomial completely.
Can someone please give me some two/three starting steps ?
I figured out that $$2a = 5-x$$And that $$a+b=2-x$$but am not getting the solution. Any further steps that may take to the solution are welcome.
Thanks a lot!